The Use of Deixis in Narrative Texts in the BSE English Textbook's "Developing English Competencies 1" - Nizar Ibnus (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2018)
Deixis as one of pragmatic features appears in every kind of text including narrative text. Deictic elements hold inseparable relation between its textual meaning and its context. This study is aimed at examining deixis in the narrative texts in BSE English textbook’s “Developing English Competencies 1” for Senior High School Grade X and explaining how they are realized in different contexts. The study uses descriptive qualitative method with five narrative texts taken as the sample for analysis. The results show that the narrative texts use all kinds of deixis, with person deixis as the most frequently used one. Person deixis enables the narrative texts to focus on the characters and the actions. Deixis is highly context-dependent that it cannot be understood without considering the context. Therefore, in comprehending narrative texts, English learners cannot only rely on their vocabularies repertoire they need also to comprehend the whole context of the story.